2021
DOI: 10.3390/ani11092719
|View full text |Cite
|
Sign up to set email alerts
|

Unmitigated Surgical Castration in Calves of Different Ages: Cortisol Concentrations, Heart Rate Variability, and Infrared Thermography Findings

Abstract: The objective was to characterize physiological responses to unmitigated surgical castration in calves of varying ages. Thirty male Holstein calves of three ages [<6 w (6W); 3 m (3M); 6 m (6M); n = 10] underwent a simulated castration treatment (SHAM) followed 24 h later by castration (CAST). For both treatments, heart rate variability, eye temperature, and cortisol were measured over time from treatment to specified end points to capture the acute response period. Interactions between treatment and age (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Tshoner et al, ( 89 ) reported a greater frequency of use of both local and systemic analgesia by veterinarians as compared with producers for surgical castration in calves but also reported that surgical castration was rated as one of the most painful procedures out of the those included in the survey; although it is challenging to compare across studies due to differences in methodology, in the current study, the pain associated with surgical castration was not rated as high. Despite substantial evidence that surgical castration causes pain in cattle (e.g., 11 13 , 54 , 57 , 61 63 ) and some regulatory guidance existing in countries outside of the United States, the provision of pain mitigation for surgical castration, although increasing has not reached full adoption as a consistently implemented best management practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tshoner et al, ( 89 ) reported a greater frequency of use of both local and systemic analgesia by veterinarians as compared with producers for surgical castration in calves but also reported that surgical castration was rated as one of the most painful procedures out of the those included in the survey; although it is challenging to compare across studies due to differences in methodology, in the current study, the pain associated with surgical castration was not rated as high. Despite substantial evidence that surgical castration causes pain in cattle (e.g., 11 13 , 54 , 57 , 61 63 ) and some regulatory guidance existing in countries outside of the United States, the provision of pain mitigation for surgical castration, although increasing has not reached full adoption as a consistently implemented best management practice.…”
Section: Discussionmentioning
confidence: 99%
“…This result is also likely in part explained by the misleading notion that younger animals feel less pain. Research has established that young animals, i.e., calves, do feel pain ( 8 , 61 , 62 ) but the response is expressed differently both physiologically and behaviorally as compared with older animals ( 12 , 13 , 57 , 63 ). Additionally, research in rats and humans has demonstrated that pain and stress events experienced as infants can have long-lasting physiological impacts ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin et al [ 103 ] did not find a decrease in the orbital temperature right after cautery disbudding, with cornual nerve blocking. Bergamasco et al [ 109 ] observed a drop in the mean temperature of the eye immediately after castration (without pain control) and sham castration. These results suggest that the decrease in the temperature of the ocular region can be related to both stress and pain responses.…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%
“…HRMs are usually fitted with a belt tied up behind the calf’s foreleg. Shaving the application site and using ultrasound gel can be used to facilitate electrode contact with the thorax [ 109 ]. The HRM usually only stays fitted in the animal during a certain phase of the trial period, around 15 to 60 min [ 81 , 109 , 118 , 119 ], in order to record the intended measurement interval, from which data can be directly obtained (Bluetooth [ 118 ]) or downloaded after to a computer [ 109 ].…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%